2011
DOI: 10.1590/s1516-35982011000700025
|View full text |Cite
|
Sign up to set email alerts
|

Production indices for dual purpose cattle in central Brazil

Abstract: -This study examined the effects of crossbreeding low genetic potential cows of Bos indicus origin characterized by Gyr crossed with Holstein-Friesian and Simmental bulls to produce animals in a low input dual purpose system. The farm is situated near Brasilia, in the savannah region of Brazil. The climate of the region is classified as Aw by Köppen.Data was available on 1580 calvings and completed lactations of cows with three genetic types: Gyr, Holstein-Friesian × Gyr and Simmental × Gyr. The bulls ran with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
(38 reference statements)
0
3
1
Order By: Relevance
“…Cardozo-Herrán et al (2019) [90], evaluating goats under similar conditions to those in this study, found similar individual milk yields in both systems; however, they obtained a higher milk yield per unit area in the MS. Bacab and Solorio (2011) [72] reported higher milk production in a traditional system, offering a greater quantity of concentrate. In a monoculture system, an average milk yield of 6.26 kg/head/day, at a stocking rate of 1 AU•ha −1 , has been reported [91], which is rather different from our data.…”
Section: Body Weight Body Condition and Milk Productioncontrasting
confidence: 99%
“…Cardozo-Herrán et al (2019) [90], evaluating goats under similar conditions to those in this study, found similar individual milk yields in both systems; however, they obtained a higher milk yield per unit area in the MS. Bacab and Solorio (2011) [72] reported higher milk production in a traditional system, offering a greater quantity of concentrate. In a monoculture system, an average milk yield of 6.26 kg/head/day, at a stocking rate of 1 AU•ha −1 , has been reported [91], which is rather different from our data.…”
Section: Body Weight Body Condition and Milk Productioncontrasting
confidence: 99%
“…In beef cattle breeding systems, mating takes place during the hottest months of the year and bulls are subject to environmental variations that may interfere with their fertility and herd reproductive effectiveness (Berry, Evans, & Parland, ; Lunstra & Coulter, ). Nevertheless, the reproductive success is one of the most important factors affecting the profitability of the cow–calf system (McManus, Louvandini, Carneiro, Lima, & Neto, ; Menegassi, Barcellos, Lampert, Borges, & Peripolli, ). Perhaps, it is always recommended, before the beginning of the breeding season, to evaluate bulls by the breeding soundness examination (BSE) that is still the most accurate and economical approach to predict fertility (Chenoweth, Hopkins, Spitzer, & Larsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…When they reach at older age, the organic capacity of the productive tract is fully developed, and nutrients are primarily directed to the maintenance and milk yield processes. As aging the animal, it has been observed a reduction in the number of secretory cells available for MY, leading to decreased function and a consequent reduction in MY (Capuco & Akers, 1999;Teodoro et al, 2000;Dobson et al, 2007;McManus et al, 2011;Baratta et al, 2017).…”
Section: Resultsmentioning
confidence: 99%